1951
DOI: 10.1002/hlca.19510340329
|View full text |Cite
|
Sign up to set email alerts
|

La constitution de l′acide hyaluronique. Sur les polysaccharides aminés III

Abstract: 1º L'acide hyaluronique de cordons ombilicaux humains a été purifié par des précipitations fractionnées, puis par des traitements selon Sevag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1951
1951
1958
1958

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…No separation was achieved when 4% of sodium borate was used in the place of the water in the mixture (4%, w/v, sodium borate-2-5 M-K2HPO4-2-methoxyethanol-33 % H3PO4; 1: 1: 1: 0-05, by vol. ), a result in agreement with the proposed structure for hyaluronic acid which contains no cis-diol groupings (Meyer, Fellig & Fischer, 1951;Jeanloz & Forchielli, 1951). Since Beale, Harris & Roe (1952) have shown that Rous-tumour RNA could be satisfactorily separated from hyaluronic acid by the use of hyaluronidase the investigation was not continued.…”
Section: B)supporting
confidence: 70%
“…No separation was achieved when 4% of sodium borate was used in the place of the water in the mixture (4%, w/v, sodium borate-2-5 M-K2HPO4-2-methoxyethanol-33 % H3PO4; 1: 1: 1: 0-05, by vol. ), a result in agreement with the proposed structure for hyaluronic acid which contains no cis-diol groupings (Meyer, Fellig & Fischer, 1951;Jeanloz & Forchielli, 1951). Since Beale, Harris & Roe (1952) have shown that Rous-tumour RNA could be satisfactorily separated from hyaluronic acid by the use of hyaluronidase the investigation was not continued.…”
Section: B)supporting
confidence: 70%